2009
DOI: 10.1177/0258042x0903400407
|View full text |Cite
|
Sign up to set email alerts
|

Changing Face of Human Resource Management: A Strategic Partner in Business

Abstract: Various approaches and models of strategic human resource management have been developed within the framework of strategic HRM. Like many theories of organization, none are complete. Rather being right or wrong each approach points to different aspect of the process needed to develop effective strategic human resource functions. The issue of fitting HR practices to business strategy has become increasingly relevant over few years. Therefore, in the present study we have made efforts to highlight various issues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…However, there is no consensus among scholars on the real impact of globalisation [22]. Globalisation is a non-stop economic process [23]and influences organisations and countries which compete for each other to competitive advantage [24]. Vladimir Pucik claimed that no firms, irrespective of size, industry and country, remain untouched from the influence of globalisation [25].…”
Section: B Globalisation and Hrmmentioning
confidence: 99%
“…However, there is no consensus among scholars on the real impact of globalisation [22]. Globalisation is a non-stop economic process [23]and influences organisations and countries which compete for each other to competitive advantage [24]. Vladimir Pucik claimed that no firms, irrespective of size, industry and country, remain untouched from the influence of globalisation [25].…”
Section: B Globalisation and Hrmmentioning
confidence: 99%
“…HR decisions can be a valuable resource for companies and have an important influence on organizational culture, capabilities, and performance (Boselie et al, 2005;Saá-Pérez and Garcia-Falcon, 2002) through human and social capital (Wright et al, 2001). In fact, research has shown that the greatest benefits occur when HR is a strategic business partner and plays an active role in developing and implementing business strategies (Bahuguna et al, 2009;Lawler and Mohrman, 2003), including the alignment of processes, competencies, and skills, helping to attain long-term strategies and goals. (Treen, 2000).…”
Section: Resource-based View Of the Firm And Hr Strategymentioning
confidence: 99%
“…McElroy (2003) points out that the process of knowledge formation includes individual and group learning, the definition of which knowledge is necessary and information gathering. We can sum up that the purpose of KM is the creation, accumulation and transformation of individual knowledge into organisational knowledge, which is used in business processes (Thierauf and Hoctor, 2006;Fuentes et al, 2007;Armstrong, 2009). Armstrong (2009) defines turnover in connection with employee satisfaction in the workplace and the sense of belonging to the organisation.…”
Section: Organisation and Knowledge Managementmentioning
confidence: 99%
“…We can sum up that the purpose of KM is the creation, accumulation and transformation of individual knowledge into organisational knowledge, which is used in business processes (Thierauf and Hoctor, 2006;Fuentes et al, 2007;Armstrong, 2009). Armstrong (2009) defines turnover in connection with employee satisfaction in the workplace and the sense of belonging to the organisation. In general, it can be understood as the final (permanent) departure of employees from the organisation.…”
Section: Organisation and Knowledge Managementmentioning
confidence: 99%